THE INFLUENCE OF ROOF COVER MATERIAL ON GABLE MODEL TO CLIMATE PARAMETERS Case Study :Rumah Instan Sederhana Sehat (RISHA), PuslitbangPermukiman, Bandung - Renita Renita; Tri Harso Karyono; Djoko Santoso (Jurusan Arsitektur - FTSP - Universitas Trisakti, 2016)
AbstractA roof should be able to prevent and reduce the radiation heat. It is more recommended if it gives a good effect in both prevention and reduction of heat. Through this research, the author wanted to know the influence of the roof covering material to gable roof style towards the climate parameters, such as temperature of humidity and heat radiation. Gable roof style is considered as more effective rather than others traditional roof style. The ability of heat reduction and humidity performances of the gable roof was tested by using Asbestos, Roof Tiles, Metal deck, and Green Roof covering material to RumahInstanSederhanaSehat (RISHA) in Centre for Housing Research and Development (PuslitbangPermukiman), Bandung. The variations of ceiling and non-ceiling were applied for knowing the result specifically in terms of the level of humidity and temperature in the room. By using quantitative descriptive method, Metal deck gave the fastest effect towards the temperature reduction, while Roof Tiles gave the best effect by using ceiling, and Green Roof gave the best effect by not using ceiling. Humidity aspect that gave the best effect occurred when using ceiling, either when using ceiling or not. Meanwhile, the lowest humidity happened when using Asbestos and Green Roof material. In the ability to reduce heat radiation, Green Roof had the best ability in reducing the heat or had worst ability in heat radiation, followed by Metal deck. Meanwhile, Asbestos covering material had the best heat radiation ability.Keywords: Roof Covering Material, Gable Roof Model, Climate (temperature, humidity, and heat radiation).